Women Emancipation in Indonesia: A Psychological desire to choose the field of physics education at the university level - Mustofa, Hisbulloh Als; Ahmad Busyairi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
Abstract: The gender bias that places women as incapable people ultimately reduces their psychological drive to engage with the field of science, especially physics. This is in stark contrast to the prevailing attitudes at universities in Indonesia. This then became the basis for the aim of this research to explore whether women's interest in studying physics education was based on psychological factors in themselves by comparing them with men. The research was conducted using quantitative survey methods, and a sampling process using random sampling was carried out on the population of a university in Indonesia. The sample was divided into two groups based on gender: 77 women and 23 men. The data collection instrument was developed using the grounded theory of planned behavior (TPB) and social cognitive career theory (SCCT), which identified four main psychological factors: identity, interest, self-concept, and self-efficacy. The results of the descriptive and inferential data analysis, conducted using one-way ANOVA, indicate that the psychological factors of identity, interest, self-concept, and self-efficacy for women are significantly higher than those for men. Furthermore, the Pearson analysis demonstrated a significantly strong positive correlation between the psychological factors tested